Sustainable periodic navigation channel assessment initiative for restricted inland waterway - Abd. Kader, Ab. Saman; Suleiman, Oladokun (2006)
The nature of human activities has remain that one thing will always complement the other. Today the world is moving so fast and but the maritime industry from issue of cybernation of ship to environmental has been quite at low frequency with development. This nitigrity is due to so called conserve nature of the industry and of course, because concerned people are blithely unaware of frequency deviation of the new generation ULCC vessel and in relation with existing channel and port situation, likewise, the international organization, focus too much of their proceedings on vessels in the deep sea, and less on port status or waterway issue. This paper will address environmental, human, and reliability factors affecting our channel in relation to ships operations, channel design, ship design and ship maneuverability in restricted channel, the need for periodic cost benefit risk assessment of restricted channel against new generation of larger class of ships that are coming to the market. The need to generate maritime environment awareness in maritime curriculum through evaluative simulation and assessment of fictitious situation that reflect real life for our channels, deduce actionable alterative options, mitigation measure and recommendation for improving the safety of navigation and protection of the marine environment by enhancing cost effective channel maintenance and controllability of ship in shallow water and restricted water.